The complete mitochondrial genome of the Cyphastrea serailia - Wentao Niu; Shuangen Yu; Bin Chen; Suharsono Suharsono (Mitochondrial DNA. Part B. Resources, 2017)
In this study, the complete mitogenome sequence of stony coral, Cyphastrea serailia (Scleractinia), has been decoded for the first time by next-generation sequencing and genome assembly. The assembled mitogenome, consisting of 17,138 bp, has unique 13 protein-coding genes (PCGs), 3 transfer RNAs, and 2 ribosomal RNAs genes. The complete mitogenome of Cyphastrea serailia showed 97% identity to Montastraea annularis. The complete mitogenome provides essential and important DNA molecular data for further phylogenetic and evolutionary analysis for coral phylogeny.